New records of Cyathus (Nidulariaceae, Basidiomycota) from conservation units in Northeastern Brazil - Francisco; dos Santos Góis, Jefferson; Goulart Baseia, Iuri (Lilloa, 2025)
The genus Cyathus (Nidulariaceae) disperses its basidiospores passively through the force of raindrops on the peridioles. These fungi play essential ecological roles in nutrient cycling and plant organic matter decomposition. Despite their wide distribution in Brazil, information on the occurrence of the genus Cyathus is still limited. In this study, new records of Cyathus were identified for the Northeast region of Brazil. Seventeen samples collected between June and August 2022 in five Atlantic Forest conservation areas in Paraíba and Rio Grande do Norte were analyzed. Four species of Cyathus were identified: C. earlei, C. limbatus, C. triplex, and C. poeppigii. Cyathus poeppigii represents the first record for the state of Rio Grande do Norte, and C. triplex represents the first records for the states of Rio Grande do Norte and Paraíba. The new records identified in this study reveal the potential distribution of the genus in the region and highlight the need for further studies, especially in poorly explored areas such as semi-arid regions.